(untitled) (The Pakistan Development Review, 1994)
Malthus (1798, 1803, 1824) wrote during the world’s first period of sustained and widespread growth in real income per person: the "Northern" agro-industrial revolution of 1740-1970. When he wrote, it was widely believed that not only growth, but also poverty reduction, depended substantially on what he called "schemes of improvement". Malthus’s central claim is that these could not reduce poverty in the long run, unless fertility declined. This, he believed, was because any short-run success of "schemes of improvement" in reducing poverty would increase the rate of population growth among the poor. This would raise the supply of labour and the demand for food. Owing to diminishing marginal returns to extra hectares-plus-persons as new, inferior land was brought into cultivation, "the proportion between the price of labour and the price of provisions" would then fall, thus returning the poor to poverty. Unless fertility fell, the long-term well-being of the poor could not improve much. Being largely dependent on the real wage, it was boxed in by the Malthus rectangle (Figure 1) of population, labour supply, land, and food, and the interactions among them.